A large unilateral basal cell carcinoma treated with Hedgehog inhibitor sonidegib: a case report - Maria Alessandra Mattioli; Valentina Benzecry; Giulia Murgia; Nerina Denaro; Angelo Valerio Marzano; Emanuela Passoni; Gianluca Nazzaro (PAGEPress Publications, 2024)
Basal cell carcinoma (BCC) is the most common non-melanoma skin cancer. BCCs are categorized into "easy-to-treat" and "difficult-to-treat" groups, with the latter including all BCCs that are challenging to manage due to technical, patient-related, or tumor-related factors, such as locally advanced BCCs. In this report, we describe an 84-year-old patient with an extensive, unilateral BCC. Following a decision by the multidisciplinary skin cancer board, the patient was successfully treated with a daily dose of 200 mg of sonidegib, an inhibitor of the Hedgehog pathway, for eight months, acquiring complete clinical and histopathological remission. No significant side effects were reported. The follow-up period of 24 months has shown no negative results.